1978
DOI: 10.1093/jn/108.6.981
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cytosolic Non Selenium-Dependent Glutathione Peroxidase Activity: Its Nature and the Effect of Selenium Deficiency

Abstract: Recent work had indicated the presence of a non selenium-dependent glutathione peroxidase activity in rat liver in addition to the selenium-dependent activity. The present study was undertaken to learn whether the glutathione S-transferases are reponsible for the non selenium-dependent glutathione peroxidase activity and to study the effect of selenium deficiency on those enzymes. Glutathione S-transferase B was purified by an established method using carboxymethyl cellulose ion exchange chromatography and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(61 citation statements)
references
References 15 publications
1
59
1
Order By: Relevance
“…They have been shown to be capable of detoxifying various endogenous and exogenous substances by conjugation with glutathione, and might act as ligands for nonsubstrate compounds such as heme and bilirubin (33). They also exhibit variable levels of nonselenium-dependent GSH-Px activity against organic hydroperoxides, but not against H202 (2,33). Human red cells have been said to contain only GSTT, a form of transferase that has a relatively low sp act with cumene hydroperoxide and therefore poor glutathione peroxidase activity (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been shown to be capable of detoxifying various endogenous and exogenous substances by conjugation with glutathione, and might act as ligands for nonsubstrate compounds such as heme and bilirubin (33). They also exhibit variable levels of nonselenium-dependent GSH-Px activity against organic hydroperoxides, but not against H202 (2,33). Human red cells have been said to contain only GSTT, a form of transferase that has a relatively low sp act with cumene hydroperoxide and therefore poor glutathione peroxidase activity (33).…”
Section: Resultsmentioning
confidence: 99%
“…These antioxidant systems include both enzymatic and nonenzymatic mechanisms. Vitamin E appears to be the most significant non-enzymatic antioxidant, and CAT, SOD, and selenium-dependent GSH-Px are believed to be the primary enzymatic systems; however, a role has also been identified recently for nonselenium-dependent glutathione peroxidase activity (I), and this appears to be a function of the GST (2).…”
mentioning
confidence: 99%
“…On the other hand, there is strong evidence for an induction of antioxidant and phase II enzymes in selenium-deficiency. Already in the late 1970s, it was reported that heme oxygenase 1 (HMOX1) [12] as well as GST activity were elevated in selenium-deficient rat liver [32]. The idea of a compensatory up-regulation of antioxidant and phase II enzymes in selenium-deficiency was further supported by findings in mice with an organ-specific targeted removal of the gene encoding for selenocysteine tRNA (Trsp).…”
Section: Introductionmentioning
confidence: 99%
“…In selenium-deficient animals a huge number of nonselenoproteins, now overwhelmingly known as Nrf2 targets, were found elevated since the late seventies (78,79,270,(395)(396)(397). The unexpected phenomenon could not be convincingly explained by GPx1 deficiency alone (396).…”
Section: Fig 6 Distinct Roles Of Redoxdependent Ubiquitination In Tmentioning
confidence: 99%